FENOMENA CHILDFREE PERSPEKTIF KONSEP MASLAHAT SAID RAMADHAN BUTHI: CHILDFREE PHENOMENA PERSPECTIVE OF THE MASLAHAT CONCEPT OF SAID RAMADHAN BUTHI - Nuriah, Nida (Mitsaqan Ghalizan, 2022)
Every married couple who gets married definitely has the goal of having children in the hope of being the successor to the family. However, along with the development of the times, a person or couple chooses to make the decision not to have children or childfree. The decision certainly raises polemic and also debate in society. From the childfree phenomenon, the author attempts to analyze childfree actions from the perspective of the Maslahat sa'id Ramadhan Al-buthi concept. Said Ramadhan al-Buthi is a Syrian scientist in the field of Islamic religious sciences and is also a very prolific writer. Al-buthi limits the use of the concept of benefit more systematically. The limitations are first, that maslahat is still within the scope of syari' goals (Maqashid al-Syar'iyyah). Second, it does not conflict with the Qur'an. Third, it does not conflict with as-sunnah. Fourth, it does not conflict with qiyas, and fifth, it does not conflict with higher benefits. If the childfree phenomenon in marriage is analyzed based on the perspective of Said Ramadhan Al-buthi's maslahat concept, then this action shows a conflict with the three points of maslahah put forward by Al-buthi namely Maqasyid As-Syari'ah, Al-Qur'an, and Hadith